Determination of some xenoestrogens in different types of personal care products using reverse phase liquid chromatography (RP-HPLC) - منصور عمار; جهينة ديب (Latakia University Journal -Basic Sciences Series, 2023)
This study aims to determine the concentration of some xenoestrogens (methylparaben and propylparaben) in some personal care products on the local market (natural creams, skin care creams, burns sweating creams and baby creams). The RP-HPLC technique was used on (C18) column, (DAD) detector at 254 nm wavelength and mobile phase:Acetonitrile/Methanol/Deionizer water(65/5/30%V/V/V). The extraction process was carried out using Dichloromethane solvent and ultrasonic device. The measurements were made after determining the ideal conditions for the chromatographic analysis process. The separation of the two compounds (MP and PP) of the samples was achieving with good selectivity (a = 2.05) and recovery ranged between (88 - 96)%. The study was done on 18 personal care products of national and imported products. The analysis results indicate the presence of both methyl paraben and propyl paraben in the most of that products, in natural skin care cream, with concentrations of (0.081 - 0.85)% , and in base cream samples with concentrations of (0.22 - 0.83)%. As well as in the baby cream samples with different concentrations range of (0.18 - 0.68)%.